EVALUASI SISTEM PENYALIRAN TAMBANG BATUBARA PADA PIT BLOCK B DI PT MINEMEX INDONESIA KABUPATEN SAROLANGUN, JAMBI - Syaifullah Aziz; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract: Based on the analysis of rainfall data for 2008-2017, the planned rainfall was 135.22 mm/ day with rain intensity in the catchment area of 21.709 mm / hour. The return period is 5 years and the hydrogeological risk is 67.23%. In the research location, PT Minemex Indonesia Pit Block B has a catchment area with an area of 48 ha, the total discharge of incoming water is 9.510 m3 / hour, with a maximum actual sump capacity of 75,867 m3 and there are three units of Coates CD200 pumps in sump with pumping discharge of 810 m3 / hour, there are two open channels and 11 main setting pond with different capacities for each compartment.After evaluating the Pit Block B mine drainage system in 2018, the Sump Capacity will be enlarged to 182,610 m3 and requires an additional 3 Coates MFC-385 pump units to obtain a total pumping discharge of 2,310 m3 / hour. PT Minemex Indonesia's Pit Block B mine drainage system is planned to have open channels that are different from the actual and settling ponds that are the same as in 2018. The effect of the mine drainage system on production is the cause of not achieving OB and Coal production. The production of OB is 293.62 m3 / BCM and Coal is 94.75 tons / hour. Keywords: rainfall, catchment area, pump, sump, open channel, settling pond, and production